Geoelectric Field Evaluation During the September 2017 Geomagnetic Storm: MA.I.GIC. Model. Issue 8 (15th August 2019) - Piersanti, M.; Di Matteo, S.; Carter, B. A.; Currie, J.; D'Angelo, G.
Abstract: The space environment near Earth is constantly subjected to changes in the solar wind flow generated at the Sun. Examples of this variability are the occurrence of powerful solar disturbances, such as coronal mass ejections (CMEs). The impact of CMEs on the Earth's magnetosphere perturbs the geomagnetic field causing the occurrence of geomagnetic storms. Such extremely variable geomagnetic fields trigger geomagnetic effects measurable not only in the geospace but also in the ionosphere, upper atmosphere, and on the ground. For example, during extreme events, rapidly changing geomagnetic fields generate intense geomagnetically induced currents (GICs). In recent years, GIC impact on the power networks at middle and low latitudes has attracted attention due to the expansion of large‐scale power networks into these regions. This paper presents a new model, called MA.I.GIC. (Magnetosphere‐Ionosphere‐Ground‐Induced Current), to derive the geoelectric field used to determine the magnitude of GICs. In addition, we discuss the results of the MA.I.GIC. model applied to the September 2017 Geomagnetic Storm with particular focus on the two sudden impulses occurring on 6 and 7 September 2017, and the two main phases on 7 and 8 September 2017. Key Points: Geoelectric field evaluation during the September 2017 Geomagnetic Storm event Discrimination between magnetospheric and ionospheric origin contribution to geoelectric field Space Weather: a new Geoelectric field model introduction